2021
DOI: 10.2169/internalmedicine.5914-20
|View full text |Cite
|
Sign up to set email alerts
|

An Adult Case of Congenital Extrahepatic Portosystemic Shunt Successfully Treated with Balloon-occluded Retrograde Transvenous Obliteration

Abstract: A 42-year-old woman visited our hospital due to syncope. Contrast-enhanced CT revealed portosystemic shunt, portal vein hypoplasia, and multiple liver nodules. The histological examination of a liver biopsy specimen exhibited portal vein hypoplasia and revealed that the liver tumor was positive for glutamine synthetase. The patient was therefore diagnosed with congenital extrahepatic portosystemic shunt type II, and with focal nodular hyperplasia (FNH)-like nodules. She had the complication of severe portopulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…All three syncope patients had some of the same characteristics including high blood ammonia, PAH and PH. Our patient is also quite different from the other syncope cases ( 11 , 14 ). Both of the other two reported cases were women.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…All three syncope patients had some of the same characteristics including high blood ammonia, PAH and PH. Our patient is also quite different from the other syncope cases ( 11 , 14 ). Both of the other two reported cases were women.…”
Section: Discussioncontrasting
confidence: 87%
“…The clinical manifestations of AM are diverse, and there are also some rare clinical manifestations, such as those with nephrotic syndrome (10) as the primary manifestation, or endocrine diseases such as hyperinsulinemia (11)(12)(13). In addition to the atypical manifestations above, there were two patients previously reported to experience syncope (11,14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Franchi-Abella et al reported that complete or partial regression of benign hepatic nodules occurred after shunt embolization in 10 children ( 5 ). Regarding adult cases, there have been two case reports of congenital portosystemic shunts with hepatic nodules that were successfully treated with endovascular shunt embolization ( 6 , 7 ). It is thought that increased portal vein blood flow related to shunt embolization normalizes the hepatic blood flow, leading to nodule reduction, but no detailed mechanism has yet been reported.…”
Section: Discussionmentioning
confidence: 99%